Cysteine biosynthesis, in concert with a novel mechanism, contributes to sulfide detoxification in mitochondria of Arabidopsis thaliana - Birke, Hannah; Haas, Florian Heinrich; Wirtz, Markus; Hell, Rüdiger (Biochemical journal, 2012)
In higher plants, biosynthesis of cysteine is catalysed by OAS-TL [O-acetylserine(thiol)lyase], which replaces the activated acetyl group of O-acetylserine with sulfide. The enzyme is present in cytosol, plastids and mitochondria of plant cells. The sole knockout of mitochondrial OAS-TL activity (oastlC) leads to significant reduction of growth in Arabidopsis thaliana. The reason for this phenotype is still enigmatic, since mitochondrial OAS-TL accounts only for approximately 5% of total OAS-TL activity. In the present study we demonstrate that sulfide specifically intoxicates Complex IV activity, but not electron transport through Complexes II and III in isolated mitochondria of oastlC plants. Loss of mitochondrial OAS-TL activity resulted in significant inhibition of dark respiration under certain developmental conditions. The abundance of mitochondrially encoded proteins and Fe-S cluster-containing proteins was not affected in oastlC. Furthermore, oastlC seedlings were insensitive to cyanide, which is detoxified by β-cyano-alanine synthase in mitochondria at the expense of cysteine. These results indicate that in situ biosynthesis of cysteine in mitochondria is not mandatory for translation, Fe-S cluster assembly and cyanide detoxification. Finally, we uncover an OAS-TL-independent detoxification system for sulfide in mitochondria of Arabidopsis that allows oastlC plants to cope with high sulfide levels caused by abiotic stresses.
Gesehen am 11.05.2017